2018
DOI: 10.1167/iovs.17-22638
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Retinal Vein Occlusion in Patients With End-Stage Renal Disease: A 12-Year, Retrospective, Nationwide Cohort Study in South Korea

Abstract: An association between ESRD and subsequent RVO development was found after adjustment for possible confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
(72 reference statements)
1
18
0
1
Order By: Relevance
“…However, we sought to determine which KT recipients retained a higher risk of RVO development. Analysis of the KT patients indicated that older age was a significant risk factor for occurrence of RVO, as shown in previous studies 11 . Our results also revealed that the CCI score, which helps to predict cardiovascular risk in KT recipients, could be a relevant risk factor for occurrence of RVO 28,29 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we sought to determine which KT recipients retained a higher risk of RVO development. Analysis of the KT patients indicated that older age was a significant risk factor for occurrence of RVO, as shown in previous studies 11 . Our results also revealed that the CCI score, which helps to predict cardiovascular risk in KT recipients, could be a relevant risk factor for occurrence of RVO 28,29 .…”
Section: Discussionsupporting
confidence: 80%
“…The Hisayama study revealed that CKD, which was defined as the presence of proteinuria and/ or eGFR < 60 mL/min/1.73 m 2 , was an independent risk factor for RVO in Japanese populations 13 . In addition, extensive, longitudinal epidemiological studies, which were performed in Taiwan and South Korea, have also suggested a strong relationship between ESRD and RVO 9,11 . Similarly, our results further verify that RVO incidence is associated with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were newly diagnosed with CRD or glaucoma were only included in the study as described in previous studies. [22][23][24][25] To test the differences of proportions that are glaucoma events, demographic factors, and other variables, between the control and CRD groups, we performed the Pearson's χ 2 test. Statistical significance was set at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…We did inclusion and exclusion of subjects and propensity matching according to the previously reported methods. [22][23][24][25] A flowchart about the selection of study subjects is shown in Figure 1.…”
Section: Study Populationmentioning
confidence: 99%
“…Few population-based studies have reported the association between patients undergoing dialysis for ESRD and the incidence of RVO. 22 23 24 25 26 27 However, a large-scale nationwide long-term cohort study of the Korean population has not been implemented. As hemodynamic changes might be different according to the method of dialysis, 28 29 the RVO incidence could be different according to the method used (hemodialysis [HD] vs. peritoneal dialysis [PD]).…”
Section: Introductionmentioning
confidence: 99%